2009
DOI: 10.2174/156720109787048212
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pegylated Lyposomal Anthracyclines and of Intra-Arterial Carboplatin and Doxorubicin Combined with Local Hyperthermia in a Case of Malignant Endovascular Papillary Angioendothelioma

Abstract: Malignant vascular tumors are exceedingly rare in childhood. Generally, their prognosis is dependent from a microscopically complete surgical resection. We observed the case of a 4-year-old boy affected by malignant endovascular papillary angioendothelioma, a rare vascular tumor of intermediate malignancy, involving all his left leg and partially the pelvis. Its very large size hampered any surgical intervention. However, we could demonstrate high sensitivity of the tumor to lyposomal anthracyclines and the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…8 Referring to the approximately 40 cases described to date, lesion size ranges from one to 40 cm in diameter, with 'typical' lesions measuring about 2-3 cm. 1,5,9 Microscopic hallmarks include amongst others the characteristic "hobnail" appearance of irregular, ectatic dermal vascular channels lined by endothelial cells with scant cytoplasm. Cytological atypia is only minimal and mitotic figures are scarce.…”
Section: Editormentioning
confidence: 99%
See 2 more Smart Citations
“…8 Referring to the approximately 40 cases described to date, lesion size ranges from one to 40 cm in diameter, with 'typical' lesions measuring about 2-3 cm. 1,5,9 Microscopic hallmarks include amongst others the characteristic "hobnail" appearance of irregular, ectatic dermal vascular channels lined by endothelial cells with scant cytoplasm. Cytological atypia is only minimal and mitotic figures are scarce.…”
Section: Editormentioning
confidence: 99%
“…5 However, subsequent studies revealed good long-term prognosis. 1,9 Nowadays, PILA is considered to represent a borderline entity between haemangioma and conventional angiosarcoma with a low-grade potential for local recurrence and metastasis. 2,3,9 Complete excision with or without local radiotherapy and regular follow-up care including assessment of regional lymph nodes is the current management of choice.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated perfused chemotherapy of osteosarcoma hyperthermally may not only effectively control the primary local tumor, but also greatly increase the rate of successful limb salvage (6,8). Although the efficacy of thermotherapy with etoposide has been extensively demonstrated in a number of tumor tissues (10)(11)(12), there are only limited studies available in the field of osteosarcoma. It is well known that the optimal therapeutic temperature clinically is 42-43˚C for 1 h (10) as this maximizes the tumor damage while preserving the surrounding normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a consensus on the enhancing effect of thermotherapy on etoposide (10)(11)(12), and positive views on the enhancing effect of thermotherapy on paclitaxel have been reported (13)(14)(15). However, there are also contrary opinions; Mohamed et al reported that the cytotoxicity of docetaxel is enhanced by hyperthermia whereas that of paclitaxel is not (16).…”
Section: Discussionmentioning
confidence: 99%